An optical fiber feeder system and performance for cellualar microcell 800MHz CDMA systems - Supachai Phaiboon (2018)
This paper proposes an optical fiber feeder system for use in cellular microcell 800MHz CDMA systems, as well as its performance. The RF signal of the CDMA system is converted into the optical signal, which can be delivered in the optical fiber. We analyze the system performance in terms of CNR (carrier to noise ratio) and SER (symbol error rate) using theoretical modeling as well as numerically calculation of the CDMA system compared with the intensity modulation. It is found that the optical feeder system for the CDMA system has got higher CNR than that of the system with intensity modulation, especially at low power level e.g. CNR more than 80dB for received optical power of -40dBm. This would provide a consequence of relatively low error rate in signal detection.